Artificial history? Inquiring ChatGPT on historiography. - Leme Lopes, A. P. (Rethinking History, 2023)
In this paper, I examine the historiographical capabilities of ChatGPT, a state-of-the-art artificial intelligence (AI) chatbot released on 30 November 2022, by OpenAI corporation. I begin by outlining a concise history of AI, highlighting the key innovations that have culminated in the development of advanced applications such as ChatGPT. Subsequently, I present an analysis of my interactions with the chatbot between February and May 2023, focusing on a long 'interview' conducted on the theory and methodology of historical science. My preliminary findings suggest that while ChatGPT holds significant potential for aiding historians in their research, the prospect of AI-driven history production remains distant and unlikely to materialize soon.